PENYELESAIAN PEMUTUSAN HUBUNGAN KERJA KARENA KESALAHAN BERAT PADA PT. SUMBER PANGAN GISINDO SLEMAN YOGYAKARTA - , Isdiana, SH, Pitaya, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Based on the formulation of the problem, then the purpose of this study was to determine how the settlement of terminatin of employment, to know whether this form of error on which the termination of employment and know what right workers have received as result of termination employment at PT. Sumber Pangan Gisindo. Research on the settlement of termination employment due to serious errors in the PT. Sumber Pangan Gisindo is a research area of law that aims to describe the fact and analyze regulations applicable laws associated with legal theory and practice of industrial relations settlement mechanism in the juridical normative legal research is done by researching the material of the positive law and its implementation in practice whose purpose is to obtain clarity regarding the application of the settlement termination employment at the company in accordance with laws an regulations. The research methode use in the writing of this thesis is by way of library researchand field research. The research library consist of data and research tools, toload the data field research, data collection, data collection tool, the preparation stage, implementation stage and completions stage. The analyze used the qualitative approach that is expected to get a picture and a clear conclusion. The research resulth/conclusions that can ce taken in case of termination employment is that both sides resolve the issue through bipartite negotiations, the mistakes made by workers is stolen prize items belonging to the enterprise and the rights of workers severance pay, gratuity working and final salary for employees working in PT. Sumber Pangan Gisindo.